Unusual clinical expression and long survival of a pseudouridylate synthase (PUS1) mutation into adulthood - Metodiev, Metodi D (Eur J Hum Genet, 2015)
A homozygote missense mutation of the pseudouridylate synthase gene was found in an adult patient with chronic sideroblastic anemia, diarrhea, microcephaly and failure to thrive. Moderate muscle weakness occurred in adulthood (6-min walk distance at 26 years: 240 m, control range 380–782 m) but a profound deficiency of mitochondrial respiratory chain complexes I and IV were found in her skeletal muscle. This, to our knowledge, is the first example of long survival of this usually fatal mitochondrial deficiency into adulthood. We suggest giving consideration to mitochondrial translation deficiency in unexplained syndromic sideroblastic anemia in adulthood.